Analysis of Student’s Scientific Writing Errors: A Case Study at Fmipa Universitas Negeri Surabaya - Sari Kusuma Dewi; Adi Maladona; Oka Saputra; Dhita Ayu Permata Sari; Nurina Rizka Ramadhania; Rudianto Artiono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Scientific writing is one of the essential skills that college students need to support research activities and the development of knowledge. However, students still encounter various challenges during the writing process. This study aimed to identify students’ responses toward scientific activities at FMIPA Universitas Negeri Surabaya and to examine the difficulties experienced by students in preparing scientific papers. The study employed a qualitative descriptive method using a purposive sampling technique. The research subjects consisted of 36 students from various study programs at FMIPA Universitas Negeri Surabaya who had been involved in research activities and scientific proposal writing. Data were collected through student response questionnaires consisting of closed-ended and open-ended questions. The data were analyzed descriptively and presented in tables and narrative descriptions. The results showed that most students had understood the existing student research programs and were familiar with the use of research guidelines. However, students still faced difficulties in systematically organizing research ideas, determining research variables and methods, finding relevant literature reviews, and connecting theories from various references. In addition, time management and the use of citation management applications were also obstacles for some students. Therefore, more structured assistance is needed through scientific writing training, reference searching training, and the use of citation management applications to improve the quality of students’ scientific writing.